A model case of a positive outcome in super‐super obesity. Issue 1 (31st January 2013) - Hipp, A.; Kramer, M.; Gallwitz, B.; Fritsche, A.; Zipfel, S.; Reutershan, J.; Niess, A.
Summary For an increasing number of obese patients, bariatric surgery is considered as the treatment of choice after the failure of conventional strategies. While numerous studies on bariatric surgery have shown substantial health benefits, there is a broad inter‐individual variation in the long‐term outcome, which is insufficiently understood. Here we show a favourable long‐term outcome following multidisciplinary care in a super‐super‐obese patient. The patient suffered from numerous typically obesity‐associated comorbidities and limitations. He underwent multidisciplinary care including two‐step bariatric intervention. Endoscopic intragastric balloon positioning was followed by gastric sleeve surgery without Roux‐en‐Y gastric bypass. His body weight dropped from 260 kg (body mass index [BMI] 79.4 kg m−2) to 85 kg (BMI 25.9 kg m−2) within 16 months and continued to be stable at 90 kg (BMI 27.8 kg m−2) at the end of the follow‐up period of 48 months. The loss of excess body weight was associated with the remission of numerous obesity‐related comorbidities and with a concomitant pronounced increase in the quality of life and in the socioeconomic status. Eventually, the patient was able to lead a normal life with a decreased risk of long‐term complications. We attribute the positive long‐term outcome to the following potential determinants: individualized bariatric surgery, multidisciplinary care, the patient's long‐term compliance, adequate adherence to the aftercare, physical exercise after surgery, family support, the cooperation of the primary care physician and the financial coverage by the health insurance. Some of these factors remain to be evaluated as predictors of a favourable long‐term outcome in prospective trials.